Circulating MicroRNAs as Promising Diagnostic Biomarkers for Patients With Glioma: A Meta-Analysis - He, Jimin; Jiang, Yao; Liu, Liang; Zuo, Zhihua; Zeng, Chun (Frontiers in Neurology, 2021)
Backgrounds and Purpose: Currently, circulating microRNAs (miRNAs) are considered to be non-invasive diagnostic biomarkers in a broad range of tumors. Nevertheless, so far, miRNAs are not fully applied to the clinic for routinely screening the glioma patients. Thus, our goal is evaluating the diagnostic performance of circulating miRNAs for glioma via a meta-analysis. The present study is registered on PROSPERO website, with the number of CRD42020195883. Methods: Literature retrieval was implemented in the PubMed, Embase, Web of Science databases using the established search strategy. We pooled the sensitivity, specificity and its 95% confidence intervals (CIs) for the included studies using Stata 14.0 software. In addition, the heterogeneity between-studies was assessed via the Q statistics and I2 values calculated by Chi-square test. A hierarchical summary receiver operating characteristic (HSROC) model was selected due to significant heterogeneity. Specifically, for exploring the factors influencing heterogeneity, we implemented subgroup and meta-regression analyses. Ultimately, Deek’s funnel plot asymmetry test was used to estimate the potential publication bias. Results: A total of 18 articles covering 24 studies were included, containing 2170 glioma patients and 1456 healthy participants. The overall pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), area under the curve (AUC) of being 0.84 (95%CI: 0.79-0.87), 0.84 (95%CI: 0.80-0.88), 5.3 (95%CI: 4.1-6.8), 0.19 (95%CI: 0.15-0.25), 27 (95%CI: 18-41), 0.91 (95%CI: 0.88-0.93), respectively. Additionally, the findings revealed that serum miRNAs and miRNA panel presented superior diagnostic performance. Conclusion: Thus, circulating miRNAs had the potentiality of serving as diagnostic biomarkers of glioma, but it needs to verify via a large pools of prospective studies. Additionally, the specific miRNAs wait for being elucidated in the diagnosis of glioma aspect, especially in early screening stage. The pathogenesis based on alteration of miRNA levels provides diagnostic and therapeutic strategies for glioma population.